Human Physiology in The Highlights of The Quran (Review of Surah Al-Tín) - Subaidah Subaidah; Idris Idris (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2023)
Allah created various kinds of creatures, both animate and inanimate. Of all His many creatures, only humans are perfect creatures created. This is stated in surah al-Tīn on the editorial ahsani taqwi>m. However, this privilege means nothing if accompanied by faith and good deeds, as in surah al-Tīn verses 5-6. So far, the interpretation of surah al-Tīn discusses human privileges from the aspects of the body and mind. According to al-Tabari> and Tantawi>>, human privilege lies in the aspect of the body. While al-Razi> said, covering aspects of the body and soul. The commentators' comments can be explained more deeply with the science of human physiology. Therefore, the author is interested in examining human privileges in surah al-Tīn based on the point of view of human physiology. Most scholars say that the editorial ahsani taqwim contains the creation of humans with physical and psychological perfection, without distinguishing between humans, except for faith and piety. Meanwhile, asfala sa>fili>n appeals to humans to use these facilities properly and correctly. Humans are just evil creatures without awareness of the importance of physical perfection. From physiology, human perfection can be seen in how the body's organs that form a system support every movement of its activities. That is, every organ will not run optimally without the system's stability in the body. For example, the brain organ's working system produces reasoning that leads people to believe in God. In addition, the brain can also create helpful technological works and innovations. However, these organs may only function if they are guarded and directed according to the will of their Creator (faith and good deeds).